Anterior Cervical Decompression, Fusion, and Stabilization by Cervical Plate and Screw for Traumatic Lower Cervical Spinal Injury: A Series of 62 Patients. Issue 1 (April 2016) - Jonayed, Sharif Ahmed; Alam, Shah; Karim, Rezaul; Chakraborty, Shubhendu; Alam, Tashfique
Introduction: Acute cervical spinal injury is one of the most common causes of severe disability and death following trauma. Though treatment of cervical spine injury is controversial but anterior cervical surgery has still a better outcome then any other method. Material and Methods: A prospective study was done in NITOR and other private clinics at Dhaka from July 2009 - September 2014. Discectomy or corpectomy was done for decompression, tricortical bone graft or cage with bone graft was used for fusion. Cervical plate was used in all. Total case was 62 (M-46, F-16). Age ranging from 14 – 52 years. Total follow up time was 3 Months to 48 Months. Quantification of deficit and neurological outcome was rated by ASIA impairment scale. Results: The results shows that peak incidence was in 3rd decade. Falling due to slip while carrying heavy load on head was the most common cause. The commonest skeletal level was C5/C6. Among 62, during the pre operative period, 6 patients had ASIA impairment scale A, 25 patients had ASIA impairment scale B, 28 had ASIA impairment scale C & 3 had ASIA impairment scale D. At follow up, 22 of ASIA B changed to ASIA D, 3 of ASIA B changed to ASIA E, 18 of ASIA C changed to ASIA D, 10 of ASIA C changed to ASIA E, 3 of ASIA D changed to ASIA E & 6 of ASIA A remain unchanged. None had worsening of neurodeficit due to surgery. Conclusion: For better outcome, proper selection of case is very important. As no neurological recovery occurs in complete lesion but for early mobilization and prevention of further complication- surgery may be considered.